Validity and sensitivity of the phonics screening check: implications for practice. (13th May 2014) - Duff, Fiona J.; Mengoni, Silvana E.; Bailey, Alison M.; Snowling, Margaret J.
<x xml:space="preserve">Abstract</x> Background Introduced in June 2012, the phonics screening check aims to assess whether 6‐year‐old children are meeting an appropriate standard in phonic decoding and to identify children struggling with phonic skills. Aims We investigated whether the check is a valid measure of phonic skill and is sensitive in identifying children at risk of reading difficulties. Sample We obtained teacher assessments of phonic skills for 292 six‐year‐old children and additional psychometric data for 160 of these children. Methods Teacher assessment data were accessed from schools via the local authority; psychometric tests were administered by researchers shortly after the phonics screening check. Results The check was strongly correlated with other literacy skills and was sensitive in identifying at‐risk readers. So too were teacher judgements of phonics. Conclusions Although the check fulfils its aims, we argue that resources might be better focused on training and supporting teachers in their ongoing monitoring of phonics.